L‐Carnitine Contents in Seafoods Commonly Eaten in Middle Eastern Countries. Issue 6 (15th June 2012) - Özogul, Yesim; Kuley Boga, Esmeray; Özogul, Fatih; Ayas, Deniz
Abstract Beta‐hydroxy‐gamma‐trimethyl amino butyric acid (L‐carnitine) content of raw and cooked seafood was determined using high‐performance liquid chromatography method. Thirty‐one different fish species and nine different crustaceans were used to compare L‐carnitine content of raw and cooked seafood. Significant differences in L‐carnitine content were found in some species, regardless of the raw or cooked seafood (P < 0.05). There were also significant differences between some of the raw and cooked species (P < 0.05). The levels of L‐carnitine in raw fish samples ranged from 17.98 mg/kg for big‐scale sand smelt to 73.07 mg/kg for European conger (Conger conger). Squid (Loligo vulgaris) and green tiger prawn (Penaeus semisulcatus) were found as the best sources of L‐carnitine among the tested seafood. Microwave cooking also significantly reduced the L‐carnitine content of some seafoods (P < 0.05). The study showed that seafoods are an important origin of L‐carnitine for covering the daily requirements of humans.